Flourishing through Prayer by Singing in a Liturgical Choir - Agnieszka Marek; Tomasz Lisiecki (Religions, 2024)
Prayer in human life enables directing attention to God and a transcendent goal beyond Earthly life. Singing has been present in the life of Israel since the oldest times, which is proved on the pages of the Holy Scriptures, in the Books of Exodus and Psalms. In the New Testament, there is a lot of encouragement to sing the glory of God in psalms and songs, as well as praising God Most High in Revelation. The Catholic Church is concerned with the quality of liturgical music through a number of recommendations and requirements defining the pieces that may become a part of the liturgy. Liturgical choir singing is a special form of common prayer. The aim of the present paper is to examine the effect of prayer by choral singing on human flourishing. The aim was achieved by analyzing recommendations of the Church on liturgical music, presenting the assumptions of the theoretical model investigating the effect of art on human flourishing, and then conducting empirical studies. Sixteen in-depth interviews were carried out with members of fourteen choirs. There were four groups of respondents according to their gender and family status. All obtained codes were organized into five main themes with four subcategories. They confirmed the assumptions of the model presented in the theoretical part and made it possible to identify the effect of choral singing on the performers’ health and the improvement of their skills. In addition, they showed a direct relation between prayer and spiritual well-being when singing in a choir, a coherence of activities with values as well as the striving for happiness.